The Factors Associated with Mothers' Preventive Measures Against Home Accidents: A Descriptive Study from Istanbul, Turkey - ILGIN, CAN; SAVE, DİLŞAD (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: One of the most common causes of death among children in Turkey is accidents, and of this, 18-25% caused by home accidents. This study aims to identify the factors associated with safety measures against home accidents, that are taken by mothers who have children between 0-6 years of age. Methods: This descriptive study was conducted among the mothers who admitted to three Family Health Centers in Istanbul, Turkey, in 2017. The data was collected with a questionnaire including The Scale for Mother's identification of Safety Measures Against Home Accidents for Children of 0-6 Years Age Group. The data was analyzed with SPSS program using Chi square, Mann Whitney-U and Spearman correlation tests (p<0,05 considered significant). 224 mothers participated in this study. Results: The most frequent home accidents were falling (48.9%), finger jam (36.6%) and crashing (30.6%). There was a weak positive correlation between the scale score and family's income (p=0.039; r=0.157); and a weak negative correlation between the scale score and child's age (p=0.001; r=-0.331). There was no association between education level of parents and safety measures. However, the scale scores were significantly higher among those who have specifically been educated about home accidents compared to those who haven't (p=0.013). Conclusion: The current education program may not be sufficient to prevent home accidents. We believe that specific courses about home accidents and safety measures are needed; even if these courses can be integrated to secondary school or university curricula it can be more beneficial.
Keywords: Turkey; home accidents; preventive measures; health education; CHILDHOOD; INTERVENTIONS; INJURIES